(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the role of coaching technologies in the sports education system, their significance in the pedagogical process, and their effectiveness in developing the professional competence of future specialists in physical education and sports. In addition, a model for developing professional competence based on coaching in sports education has been developed, and its structural components, pedagogical conditions, and practical mechanisms are analyzed. The study highlights the importance of modern pedagogical technologies, interactive methods, and motivational approaches in training sports professionals.